Patient satisfaction and reported outcomes on the management of actinic keratosis - Khanna R; Bakshi A; Amir Y; Goldenberg G (Dove Medical Press, 2017)
Raveena Khanna,1,2 Anshika Bakshi,3 Yasmin Amir,1 Gary Goldenberg1 1Department of Dermatology, Icahn School of Medicine at Mount Sinai, New York, NY, 2Creighton University School of Medicine, Omaha, NE, 3Rutgers Robert Wood Johnson Medical School, Piscataway Township, NJ, USA Abstract: Actinic keratosis (AK) is a common dermatologic condition in which hyperplastic epidermal lesions develop in response to excessive and chronic exposure to ultraviolet (UV) radiation. If left untreated, AK can progress to squamous cell carcinomas of the skin. Incidence is rising worldwide as a result of the progressive aging of populations and an increase in lifetime cumulative exposure to UV radiation. Currently, various treatment options exist, which range from topical medications to light-based therapies and procedural modalities. In this article, we will review the treatment options for AK with a focus on assessments of patient satisfaction with treatment. Keywords: actinic keratosis, treatment, outcomes, patient satisfaction, quality of life